Functional and structural changes in gray matter of parkinson's disease patients with mild cognitive impairment. Issue 93 (August 2017) - Chen, Boyu; Wang, Shanshan; Sun, Wenge; Shang, Xiuli; Liu, Hu; Liu, Guohao; Gao, Jie; Fan, Guoguang
Abstract: Background and purpose: Cognitive impairment is a common non-motor complication of Parkinson's disease (PD). To investigate cognitive-related changes of gray matter (GM) structure and function in PD using voxel-based morphometry (VBM) and resting state functional connectivity (RSFC). Materials and methods: Resting state functional magnetic resonance imaging (rs-fMRI) and 3D-T1-weighted MRI scans were obtained from 21 PD patients with mild cognitive impairment (PD-MCI), 11 PD patients with normal cognitive function (PD-NC), and 21 healthy controls (HC). Functional connectivity (FC) was analyzed by defining the posterior cingulated cortex (PCC) as the seed region. VBM was performed to assess patterns of GM atrophy. Results: In PD-NC versus HC, results indicated decreased PCC-FC in the right temporal gyrus(TG) and increased PCC-FC in the left medial temporal lobe(MTL), bilateral precuneus(Pcu), and parieto-occipital junction(POJ), as well as GM atrophy in the bilateral prefrontal-striatal circuit(pFTSC), TG and Pcu. In PD-MCI versus PD-NC, decreased PCC-FC was found in the bilateral prefrontal cortex(PFC), left POJ, and right TG. In addition, PCC-FC of the bilateral Pcu and GM volume of the left MTL, bilateral TG, and PFC were positively associated with cognitive score. Conclusions: Structural and functional damage of the PFC and temporal lobe are associated with subtle cognitive decline in PD, while functional enhancement of the MTL and POJ is involved in normal cognitive function of PD. In addition, the combined application of rs-fMRI and VBM analysis might become an effective means to investigate cognitive impairment-related GM abnormalities in PD-MCI patients prior to development of dementia.